Deformation and texture evolution of OFHC copper during dynamic tensile extrusion. (1st May 2015) - Hörnqvist, M.; Mortazavi, N.; Halvarsson, M.; Ruggiero, A.; Iannitti, G.; Bonora, N.
Abstract: During dynamic tensile extrusion (DTE) the material is subjected to a complex deformation history, including high strain rates, large strains and elevated temperatures. This technique provides unique means to explore material performance under extreme conditions. In this work, the microstructural evolution of 99.98% commercially pure copper during the DTE test was investigated by means of electron backscatter diffraction (EBSD). The investigation was focused on the segment of the extruded jet that remained in the die, since numerical simulation showed that material points along the longitudinal axis of such segment correspond to different stages of a common temperature compensated deformation history. Therefore, post mortem microstructure information extracted at different locations along the center line is equivalent to in situ real-time measurement during the deformation process. EBSD investigations along the center line showed a progressive elongation of the grains, and an accompanying development of a strong 〈0 0 1〉 + 〈1 1 1〉 dual fiber texture. Meta-dynamic discontinuous dynamic recrystallization (DRX) occurred at larger strains, and it was demonstrated that nucleation occurred during straining, while subsequent grain growth took place during post-deformation cooling in the die. According to strain energy minimization arguments, the recrystallization resulted in an increased 〈0 0 1〉 texture component. The critical strain for recrystallization was well predicted from a power-law dependence on the Zener–Hollomon parameter, including grain size dependence and a temperature dependent activation energy. In addition, it was shown that 〈0 0 1〉 and 〈1 1 1〉oriented grains develop different dislocation substructures during straining, exhibiting elongated cells/micro-bands and typical cell structures, respectively. The present results also confirm that dynamic tensile ductility increases with decreasing initial grain size as a result of grain refinement and lowering of dislocation and twin densities during DRX.